Healing potentiality of blood clot, S-PRF and A-PRF as scaffold in treatment of non-vital mature single rooted teeth with chronic peri-apical periodontitis following regenerative endodontic therapy: randomized clinical trial - Omnia Badawy Darwish; Said Mohamed Abdel Aziz; Hany Samy Sadek (BMC Oral Health)
Abstract Objectives This randomized prospective controlled trial investigated the effectiveness of different strategies of regenerative endodontic therapy on necrotic mature anterior teeth with chronic periapical periodontitis with 18 months follow up. Methods A total analyzed 51 adult participant with mature single rooted teeth having necrotic pulp with chronic periapical periodontitis (PAI ≥ 3) were selected. Patients had been randomly categorized into three distinct groups (n = 17 each group). All groups received the same treatment on the first visit. After 2 weeks, regenerative treatment was performed using either blood clot technique, Standard-PRF and Advanced-PRF approach. A standardized radiograph was taken, and the patients instructed for 6, 12 and 18 months follow up periods. Fisher's exact test was applied to compare the frequency of PAI scores at different follow-up intervals between the three groups. Results The results showed radiographic success at 18 months (58.8% in blood group, 94.1% in S-PRF group and 76.5% in A-PRF group). There was no statistically significant difference between the three groups according to incidence of healing at 6, 12 and 18 months. Clinical success was 82.4% in blood group and 88.2% in both S-PRF and A-PRF groups. There was no significant difference between the three groups (p = 1). The overall success (clinical and radigraphic) was 76.5%. Incidence of the gaining sensitivity after 12 and 18 months was 29.4% with A-PRF group and 41.2% within the S-PRF group, 17.6% with BC group. Conclusion PRF based regenerative technique may outperform the blood clot technique in treatment of non-vital mature teeth with chronic periapical periodontitis. There is a need for future randomized clinical studies to consolidate procedures in this field with more prolonged evaluation periods. Clinical trial registration The study was retrospectively registered with ClinicalTrials.gov (ID: NCT04606719 ) in 28/10/2020.